2018
DOI: 10.1111/bcpt.13033
|View full text |Cite
|
Sign up to set email alerts
|

A Focus on Macitentan in the Treatment of Pulmonary Arterial Hypertension

Abstract: The approval of macitentan has increased the number of pharmacological treatments of pulmonary arterial hypertension (PAH). Here, we review the effect on PAH of macitentan compared to other endothelin receptor antagonists. Drugs targeting the endothelin (ET) pathway include the selective ET receptor antagonist ambrisentan, the ET /ET receptor antagonists, bosentan and macitentan, which were recently approved for PAH treatment. Macitentan exhibits higher antagonistic potency than bosentan and ambrisentan in pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…At the cellular level, the drug differs from bosentan and ambrisentan through its binding profile, namely its slow receptor dissociation characteristics [36]. Due to this quality, macitentan theoretically has the potential to block ET-1-induced signaling more effectively than other ERAs [37].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the cellular level, the drug differs from bosentan and ambrisentan through its binding profile, namely its slow receptor dissociation characteristics [36]. Due to this quality, macitentan theoretically has the potential to block ET-1-induced signaling more effectively than other ERAs [37].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Macitentan is administrated orally once daily, with a usual dosage of 10 mg [41]. The drug is slowly absorbed, reaching C max approximately 8 h post-dose, and more than 99% is bound to plasma proteins [37]. Although the bioavailability is unknown, data from physiologically based pharmacokinetic modelling indicates high oral bioavailability.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolite of macitentan was analysed by ultra performance liquid chromatography-tandem mass spectrometry. Key finding Most CYP3A4 protein variants () exhibited a sharp decrease, meanwhile nearly one in five variants (CYP3A4.3,.4,.5,.10,.15,.16) showed a significant rise in intrinsic clearance. The relative clearance of CYP3A4 protein variants was ranged from 5.53 to 501.00%.…”
mentioning
confidence: 92%
“…Compared to the selective ETA receptor antagonist ambrisentan, the ETA/ETB receptor antagonists bosentan, macitentan exhibits higher antagonistic potency, has a longer duration of action, reflected by the longer half-life, as well as pharmacodynamics attributed to its active metabolite, and exhibits less adverse effects. [5] Except treating PAH, Tullos et al also found macitentan had an ability to decrease renal injury by protecting renal microenvironment. [6] Cytochrome P450 (CYP450) is considered to be one of approaches to metabolite a large quantity of drugs.…”
Section: Introductionmentioning
confidence: 99%